Penerapan Metode System Usability Scale untuk Analisis UI/UX Website UMKM Lancar Jaya Food - Fariyono Fariyono; Wisnu Sanjaya (JITU : Journal Informatic Technology And Communication, 2023)
Digitization of Micro, Small, and Medium Enterprises in Indonesia is still not optimal. The lack of full digitalization, besides the HR competency factor, is the unequal distribution of supporting infrastructures such as internet access and transportation. The use of IT in MSMEs is slowly but surely starting to show an increase. Generally, MSME actors use social media as a marketing and promotion medium. In addition to social media, MSMEs have also begun to use the Website as a marketing and promotion medium. However, due to the lack of MSMEs' ability to manage Websites, it is a challenge. As a result, the use of the Website is not optimal and inefficient because orders still use social media such as WhatsApp for buying and selling transactions. The purpose of this study is to analyze the UI/UX of the Lancar Jaya Food MSME Website, especially on the buying and selling features, using the System Usability Scale method. As a result, the System Usability Scale score obtained a value of 73.35, representing Acceptability Ranges with an Acceptable value. Then the adjective rating with a value of Good and Letter Grade with a value of B.